Dynamic analysis of platinum material flows and stocks with hybrid MFA method aiming to carbon neutral targets of automotive industry in China. Issue 1 (1st January 2021) - Zhang, Yana; Liu, Yingying; Lv, He; Chen, Sha; Li, Sumei
ABSTRACT: Platinum is a key material in the automotive industry. In this study, we first quantitatively analyzed the platinum cycle from 2009 to 2019 in the automotive industry in China. The stocks of platinum to 2050 were then evaluated under different scenario in the automotive industry. The total amount of platinum entered into the automotive industry was 145.77 t from 2009 to 2019. Among them, the in-use stocks of platinum in vehicles increased from 37.07 t to 133.78 t.Platinum stocks in the automotive industry under 2°C scenario for high-, baseline- and low-demand in 2050 are 712.97 t, 529.32 t, and 345.67 t, respectively, while under carbon-neutral scenario, it is 440.55 t, 327.42 t and 214.30 t, respectively. Under the carbon-neutral scenario, the platinum stocks in gasoline and diesel vehicles in 2035 and 2050 will decrease, which can provide 61.41% and 49.92% of the platinum stocks for fuel cell and hybrid vehicles in 2035 and 2050, respectively.